PENGEMBANGAN MANAJEMEN KURIKULUM DAN PEMBELAJARAN DI PONDOK PESANTREN MINHAJUSSALIKIN - Mufasirul Bayani (JIP: Jurnal Ilmu Pendidikan, 2024)
The rapid development of information technology forces educational institutions to adapt quickly. Administrators and educational practitioners need to innovate in managing curriculum and learning to develop students' talents and interests, and ensure that graduates have competencies that are in accordance with the demands of the times. Effective learning management organizes content and activities according to students' needs while paying attention to individual differences, with a focus on developing critical thinking and managerial skills and utilizing information technology. Teachers play a key role in curriculum implementation. Effective educators are able to apply and assess curriculum intuitively. Curriculum development can be spontaneous and reflective, involving the experiences and reflections of curriculum developers. The balance between various curriculum models is important, and the socio-political context of the school must also be considered to improve the quality of education. This study examines the development of curriculum management and learning at the Minhajussalikin Islamic Boarding School, Banyuwangi. The curriculum at Minhajussalikin combines national standards with elements of Islamic education, aiming to produce students who are experts in science and religion. This study answers two main questions: the principles of curriculum management and learning development, and its implementation at Minhajussalikin. The findings are expected to provide insights for educational practitioners. The methodology used is a case study with a qualitative approach, collecting data through interviews and document analysis. Data were analyzed using the Miles and Huberman qualitative analysis model, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that Minhajussalikin has succeeded in integrating Islamic values ​​with modern educational practices to develop students who are balanced and contribute positively to society.